STRATEGIC PROFILING & ANALYTIC MODELLING OF NODE MISBEHAVIOR IN MANET BASED IOT PARADIGM THEORY - Olanrewaju, Rashidah Funke; Najeeb, Athaur Rahman (2018)
Ubiquitous Computing and Internet of Things (IoT) are extremely popular in recent age and therefore imparting high level security mechanism is highly indispensable for such advanced technical systems. Game Theory acts as a suitable tool offering promising solutions to securityrelated concerns in Mobile Ad-Hoc Networks (i.e., MANETs). In MANETs, security forms a prominent concern as it includes nodes which are usually portable and require significant coordination between them. Further, the absence of physical organisation makes such networks susceptible to security breaches, hindering secure routing and execution among nodes. Coordination among nodes during communication and working without control of any central manager truly ensembles them to be applied in IoT. However, the identification and later mitigation of malicious nodes becomes an immensely difficult task especially when Selfish/Erroneous nodes exist along with normal Collaborative nodes in the Regular camp. Game Theory approach has been manipulated in the current study to achieve an analytical view while addressing the security concerns in MANETs. This study considers selfish nodes in the regular node camp while modelling the Regular versus Malicious node game and thereby enhancing the prior mathematical schema of strategical decision making to accommodate for the same. The proposed study performs statistical analysis and presents a mathematical model to mimic the multi-stage game between regular and malicious node using Game Theory. The simulation of the model has proved that the Perfect Bayesian Equilibrium outshines other approaches used in this study, specifically pure strategy and mixed strategy. The utility of both regular and malicious node has improved noticeably when nodes adopt PBE strategy. The framework tries to effectively represent the various unpredictable actions of node cooperation, node declination, node attacks as well as node reporting that can model the strategic profiling of various mobile nodes. Understanding the patterns and then deploying the algorithms in security products can reduce intrusion to a greater extent.